Quality of life as a predictor of hospitalization in patients with chronic kidney disease on hemodialysis: retrospective cohort - DIPP, THIAGO; Pereira, Gabriela Alves; Segatto, Karina; Baumgarten, Maria Cristina dos Santos; Silva, Vanessa Giendruczak; Plentz, Rodrigo Della Méa (Clinical and Biomedical Research, 2019)
Introduction: As medical advances are achieved in the care of people with chronic illnesses, there an increasing evidence that health-related quality of life (QoL) is associated with poor outcomes including hospitalization and death. The aim of study was assessed quality of life as predictor of hospitalization in chronic kidney disease (CKD) patients on hemodialysis (HD). Methods: A retrospective cohort of 108 patients with CKD on HD followed up for 24 months. The QoL was assessed by the Kidney Disease and Quality of Life Short-Form (KDQOL-SF), including the time to first hospitalization and death as outcomes. Results: The highest scores in the KDQOL-SF were in "sexual function", "team stimulation" and "cognitive function", while the lowest scores were in "professional role", "physical function" and "energy/fatigue". An association was observed between low scores in "overall health" and "emotional function” domains with reduced time until first hospitalization. Higher scores in the domains "cognitive function" and "social support" reduced in 77% and 71%, respectively, the risk of death in this population. Conclusion: The QoL demonstrate that can be used to predict hospitalization in CKD patients on HD, but the results were not sufficient to define it as predictive of mortality.